Back to the land - new hope for civil servants and graduates - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Young jobless graduates and the unemployed are starting up small farms in great numbers. Their educational background stands the former in good stead. They have the will to earn a good living, and so they breathe new life and inspiration into the...